Bioprospecção de actinobactérias endofíticas com potencial antimicrobiano isoladas de Theobroma cacao - Pinto, Lívia Freitas da (Universidade Federal de São Carlos, 2023)
Actinobacteria constitute one of the largest bacterial phyla and are classified as Gram-positive bacteria, being ubiquitous in aquatic and terrestrial ecosystems. They are recognized for their ability to produce secondary metabolites with different functionalities, among which are bioactive compounds with antimicrobial activity. This study bioprospecting and identification of endophytic actinobacteria isolated from Theobroma cacao grown in the region of Paragominas, Pará. region of Paragominas, Pará, Brazil and evaluated the biotechnological potential of these strains in the production of antimicrobial agents. After isolation, it was possible to verify the presence of 11 distinct endophytic bacteria. bacteria. The identification of these isolates, determined by phenotypic analysis and molecular characterization, proved that 4 of the 11 belonged to the actinobacteria group, and these were classified at the level of Microbacterium (3 strains) and Curtobacterium (1 strain). The other isolates were characterized as Pseudomonas (2 strains), Bacillus (1 strain), Ralstonia (1 strain) and Methilobacterium (3 strains). The 4 strains from the Actinobacteria phylum were submitted to the antimicrobial activity evaluation test activity. All of them inhibited the growth of Staphylococcus aureus (inhibition halos diameters ranged from 2.3 to 3 cm), proving to be effective against this Gram-positive bacterium. However, they showed no activity against Escherichia coli.
Bioprospecting endophytic actinobacteria with antimicrobial potential isolated from Theobroma cacao
Keywords: Actinobactérias; Metabólitos secundários; Bioatividade; Atividade antimicrobiana; Actinobacteria; Secondary metabolites; Bioactivity; Anti-bacterial activity; CIENCIAS BIOLOGICAS::MICROBIOLOGIA